Native fish conservation in Nepal: Challenges and opportunities - Gurung, Tek Bahadur (Nepalese Journal of Biosciences, 2013)
Habitat degradation and loss probably has been more responsible for the decline of native fish species. Nepalese fishes are one of main aquatic vertebrates which are yet to be studied for their occurrence, distribution and ecology, especially from western regions of the country. However, before complete understanding on native fishes, threat over their existence have been loomed by climate change, over fishing, pollution, alteration of natural habitats and poor understanding of fish ecology etc. Thus, publicizing the importance and knowledge of fish conservation has been one of the most important challenges. The other challenges are sustainability of quality and quantity of freshwaters which have been impacted. In such circumstance to overcome the problems, adoption of community or cooperative based conservation could be one of the best approaches for freshwaters and fish restoration. Optimistically, a national strategy on conservation of freshwater fish is desirable. Fish conservation has the opportunities to be used for multidimensional purposes. A success of single fish species might contribute substantially on local economy, if that could be used in aquaculture or angling for tourism industry. DOI: http://dx.doi.org/10.3126/njbs.v2i0.7492 Nepalese Journal of Biosciences 2 : 71-79 (2012)